Dynamic niche partitioning in root water uptake facilitates efficient water use in more diverse grassland plant communities. (4th September 2017) - Guderle, Marcus; Bachmann, Dörte; Milcu, Alexandru; Gockele, Annette; Bechmann, Marcel; Fischer, Christine; Roscher, Christiane; Landais, Damien; Ravel, Olivier; Devidal, Sébastien; Roy, Jacques; Gessler, Arthur; et al.
Abstract: Efficient extraction of soil water is essential for the productivity of plant communities. However, research on the complementary use of resources in mixed plant communities, and especially the impact of plant species richness on root water uptake, is limited. So far, these investigations have been hindered by a lack of methods allowing for the estimation of root water uptake profiles. The overarching aim of our study was to determine whether diverse grassland plant communities in general exploit soil water more deeply and whether this shift occurs all the time or only during times of enhanced water demand. Root water uptake was derived by analysing the diurnal decrease in soil water content separately at each measurement depth, thus yielding root water uptake profiles for 12 experimental grasslands communities with two different levels of species richness (4 and 16 sown species). Additional measurements of leaf water potential, stomatal conductance, and root traits were used to identify differences in water relations between plant functional groups. Although the vertical root distribution did not differ between diversity levels, root water uptake shifted towards deeper layers (30 and 60 cm) in more diverse plots during periods of high vapour pressure deficit. Our results indicate that the more diverse communities were able to adjust their root water uptake, resulting in increased water uptake per root area compared to less diverse communities (52% at 20 cm, 118% at 30 cm, and 570% at 60 cm depth) and a more even distribution of water uptake over depth. Tall herbs, which had lower leaf water potential and higher stomatal conductance in more diverse mixtures, contributed disproportionately to dynamic niche partitioning in root water uptake. This study underpins the role of diversity in stabilizing ecosystem function and mitigating drought stress effects during future climate change scenarios. Furthermore, the results provide evidence that root water uptake is not solely controlled by root length density distribution in communities with high plant diversity but also by spatial shifts in water acquisition. A plain language summary is available for this article. Abstract : Plain Language Summary